Social and programmatic vulnerability in the context of transgender people’s health: a scoping review of scientific evidence from Brazil - Francisca Lidiane Sampaio Freitas; Ximena Pamela Claudia Díaz Bermúdez; Edgar Merchán-Hamann; Adriano Santiago Dias dos Santos; Victor Fonseca Vieira (International Journal for Equity in Health)
Abstract Background Most transgender people face different conditions of health vulnerability on a daily basis. In the Brazilian context, no research review has been found on such situations in the light of the theoretical conceptualization of multidimensional vulnerability. This research aimed to identify and analyze components of social and/or programmatic vulnerability that interfere with access to health care for trans people in Brazil. Methods The scoping review followed the JBI Manual and the PRISMA-ScR list. Brazilian studies published in any language, in the period 2019-April 2023, in the NCBI/PubMed, Web of Science, EMBASE, Scopus, SciELO, and LILACS databases were selected. The inclusion criteria included: original research with a sample of transgender people aged 18 years and over; and research contemplating conditions of social and/or programmatic vulnerability. Three reviewers independently selected the articles. The extracted and mapped data included components of these dimensions, according to the theoretical framework, as well as characteristics of the studies, for the synthesis of the descriptive analysis. Results A total of 46 studies were included. Social and programmatic vulnerability components were present in 67% of the studies. Among the main findings, the social dimension included discrimination, situations of violence in different contexts and social exclusion; prejudice and school dropout, homelessness, informal work and precarious income; and harmful use of alcohol and/or other drugs. The programmatic dimension encompassed disrespect for the use of the social name and institutional discrimination; hormone therapy without professional monitoring and scarcity of specialized services; lack of integration between Primary Health Care (PHC) and specialized care and insufficient PHC involvement; distortions between what is contained in public health policies and the practice in the services. A higher percentage (61%) of studies with trans women and 7% with trans men were observed; inequalities in regional distribution; predominance of HIV and AIDS and mental health themes; and similar percentages in the various methodological approaches and publications in national and foreign journals. Conclusion The identified situations of vulnerability contribute mainly to supporting the formulation and implementation of new public policies in comprehensive health that are more comprehensive and inclusive, which mitigate the current social and health inequities.